2021
DOI: 10.24926/iip.v12i2.3699
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Copenhagen Burnout Inventory in Pharmacists

Abstract: Objectives: This study aimed to 1) determine the validity of the Copenhagen Burnout Inventory (CBI) for use in the assessment of burnout in a sample of pharmacists using confirmatory factor analysis (CFA), and 2) use the CBI items and other measures of work-life to assess burnout in pharmacists employed in various types of practice. Methods: A cross-sectional survey was administered to a sample of 2,582 pharmacists in a single Midwestern US state. The survey included the three subscales of the CBI, each of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 48 publications
(72 reference statements)
5
16
0
Order By: Relevance
“…Similarly, CPs with limited work experience suffered from a higher level of burnout. This trend is consistent with the ndings of a study conducted among pharmacists in the United States [63]. Such a result could be explained by the fact that older CPs learned from their life experience and previous encounters with stressful events how to anticipate, cope and prepare for potentially tough situations.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, CPs with limited work experience suffered from a higher level of burnout. This trend is consistent with the ndings of a study conducted among pharmacists in the United States [63]. Such a result could be explained by the fact that older CPs learned from their life experience and previous encounters with stressful events how to anticipate, cope and prepare for potentially tough situations.…”
Section: Discussionsupporting
confidence: 89%
“…[ 25 ] A study published in 2021 also confirms its validity and reliability as an instrument to assess burnout in pharmacists in different practice settings. [ 26 ] Since little is known about pharmacists’ burnout in Kuwait and the Eastern Mediterranean region, this study may provide novel data. These data are imperative to guide the development of support strategies to empower pharmacists and other healthcare workers to face these challenging global health crises.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a previously published study that showed that the incidence of burnout in healthcare employees appears more in 30- to 40 years old and in those who are in their early career. [ 5 , 26 , 28 , 30 ] This suggests that age is a protective measure against burnout. This could be explained by the fact that older pharmacists manage difficult situations better than their younger counterparts as their previous exposure to stressful situations increases their ability to deal with them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, pharmacists at community pharmacies reported the lowest average professional fulfillment and highest average work exhaustion and interpersonal disengagement compared to pharmacists in other work settings. This could be due to the increased demand for dispensing and prescription management services, such that community pharmacists are taking less time than they desire to provide more patient care [36,37]. While this comparison suggests an inverse relationship between professional fulfillment and burnout, other research suggests that the absence of burnout does not necessarily lead directly to professional fulfillment [7].…”
Section: Assessing Pharmacists' Professional Wellbeing Across Pharmacists' Work Settingmentioning
confidence: 92%